The Effect of Humor Therapy on Relieving Quality and Fear of Pain in Elderly Residing Nursing Homes: A Randomized Clinical Trial - Behrouz, Shohre; Mazloom, Seyed Reza; Kooshiar, Hadi; Asgharipour, Negar; Aghebati, Nahid; Behnam Vashani, Hamid Reza (Advances in Nursing & Midwifery, 2019)
Introduction: Chronic pain is common in the elderly. Distraction is one of the important uses of cognitive-behavioral techniques and humor is one of the distraction techniques used in pain control. The aim of the present study was to determine the impact of humor therapy (HT) on quality and fear of pain in nursing homes. Methods: We conducted a randomized clinical trial study on 55 elderly who had experienced chronic pain for at least 3 months and residing in nursing homes in Mashhad, Iran, 2016. The sampling was of convenience type as well as random allocation of nursing homes to two groups; the one receiving HT (n = 28) and a control group (n = 27) living in two similar nursing homes. The experimental group received 6 sessions of humor therapy over 6 weeks and the control group received the routine care. To this end, pain quality and fear of pain were assessed at the first, after the 3rd and 6th sessions in both groups respectively using the McGill Pain Questionnaire and Fear of Pain Questionnaire. The main data were also compared using the Mann-Whitney U test. Results: Total pain quality and fear of pain before the study was homogeneous in both groups (P > 0.05); but after 6th sessions in humor therapy the score of total pain quality decrease from 3.5 ± 1.1 to 2.4±0.7 (P < 0.001) and the score of fear of pain decrease from 36.0 ± 1.4 to 30.6 ± 0.8 (P < 0.05). These results were not significant in control group (P > 0.05). Conclusions: HT as a low-cost method can be an effective way to reduce the quality and fear of pain in elderly pain.